The Private World of Ottoman Women: By Godfrey Goodwin (London: Saqi Books, 2006. 261 pages.) (American Journal of Islam and Society, 2006)
The publication of The Private World of Ottoman Women is an importantlandmark in both social and gender history. Until this point, accounts of the seemingly mundane activities of Ottoman women were limited to travelers’accounts, gossip, and information that could be discerned through the latticeworkguarding the imperial harem. Godfrey Goodwin’s groundbreakingwork, however, introduces the reader to a society with women who were, inmany areas, their husbands’ peers and, although restrained by certain genderedrestrictions, had a remarkable level of mobility. His book not onlyremoves the popular notion that “Ottoman woman” is synonymous with“harem girl,” but shows that there was an extensive network of politics,intrigue, and socio-religious change and adaptation outside of the urban elite.It also presents the reader with an understanding, although not overemphasized,that these were women who lived within the parameters of Islam asboth Christian and Muslim women, and who distinctly embodied the idealsof the feminine in Islam.The book is cleverly organized to reflect both the chronology of theempire’s development and its class hierarchy. The majority of the first twochapters, “The Coming of the Nomads” and “The Wanderers,” discuss indepththe empire’s early formation and the pre-Islamic period of tribalnomadism, and essentially illustrate the empire’s boundaries and seeds ofsocial activity. Thus they are not terribly informative about Ottoman women.But this is in no way the fault of the author, who does provide some interestingtidbits where information could be gleaned and placed into the contextof the thesis ...